“Europeana Newspapers“ project Workshop on the Texts Refinement and Quality Assesment - Trtovac, Aleksandra (Infotheca - Journal for Digital Humanities; Vol 14 No 1 (2013): Infotheca - Journal of Informatics and Librarianship, 2024)
University Library "Svetozar Markovic" in Belgrade is one of the 18 full partners in the project "Europeana newspapers" along with the most important national and university libraries of Europe and LIBER, German company CCS1 , and 11 associated partners. Within the project, at the University Library in Belgrade on 13 and 14 June 2013 the workshop on the assessment of the quality and refinement of digitized newspaper articles was held.